Birefringence of flow-assembled chitosan membranes in microfluidics. (30th June 2017) - Li, K; Correa, S O; Pham, P; Raub, C B; Luo, X
Abstract: Biopolymer membrane assembly in microfluidics offers precise spatial and temporal resolution for biomolecular and cellular interactions during and after assembly. Control over molecular transport across the biofabricated membranes requires microstructural characterization. This study investigates, for the first time, the birefringence of chitosan membranes assembled with flow in a microfluidic environment, and the effects of pH and flow rate on the membrane's micro-alignment. The optical anisotropy of the formed membranes was quantified using a de Sénarmont compensator for transmitted quantitative polarized light microscopy. The chitosan membranes were biofabricated within a small aperture in a microfluidic network with various flow and pH conditions of chitosan and alginate solutions. The measured optical retardance and parallelism index clearly indicate that the microstructure of the flow-assembled membrane was well organized and aligned along the direction of chitosan flow. Optical retardance increased significantly with the pH of the alginate solution, but was less sensitive to the variation of the flow rates of the polymer solutions during the biofabrication process. It was also determined that the birefringence signal dropped significantly across the membrane growth direction regardless of the molecular density in the membrane. The mechanism of the micro-alignment was discussed, which was presumably due to the molecular un-wrapping by shear flow. We envision that the current study paves a path to further understand and actively manipulate the microstructure of flow-assembled membranes for broad lab-on-a-chip applications.